Kučar Železnodobno naselje in zgodnjekrščanski stavbni kompleks na Kučarju pri Podzemlju = Eisenzeitliche Siedlung und frühchristlicher Gebäudekomplex auf dem Kučar bei Podzemelj - Ciglenečki, Slavko (Opera Instituti Archaeologici Sloveniae, 1995)
Kučar near Podzemelj represents one of the most significant archaeological sites not only in Slovenia but also in the wider southeastern alpine region. It is an extensive complex composed of an Iron Age and Late Roman settlement upon the hill Kučar, as well as numerous necropoli that are distributed throughout the villages of Podzemelj, Zemelj, Škrilje and Grm. The site is well-known all over the world for its elaborate material finds originating from the cemeteries there. The book presents the results from rescue excavations that were carried out between the years 1975 and 1979 on the northern top of Kučar by the Institute for Archaeology. Substantial remains of a settlement dating to the Early and Late Iron Ages (8th -1st centuries BC) were excavated, as well as the even more surprising discovery of an Early Christian building complex (5th century AD) incorporating two churches, a baptistery and a large building with an enclosing wall that was reinforced with two towers. This publication concerning the settlement on Kučar near Podzemelj is the third monograph regarding this site. The first two publications presented the material finds from the Iron Age necropolis, preserved at the National Museum in Ljubljana and at the Museum of Natural History in Vienna. This third publication includes a contribution by Metka Culiberg and Alojz Šercelj on the investigations of organic remains from Kučar.